School dropout among semai pupils : case study :Sekolah Rendah Satak, Rabu Pahang - Amy Marina, Akim. (Universiti Malaysia Sarawak (UNIMAS), 2009)
School dropout among the school children of Orang Asli are increase every year as can be shown their participation in secondary and high education level is decrease. From the primary level, school dropouts start to happen. The purpose of this research is to find out what factors contribute to school dropout in Semai pupils. The factors have link with the psychosocial, parents, cultural and environment in which influence the students to dropout from school. The research being conducted as case study in Sekolah Rendah Satak, Raub Pahang and the respondents are among the pupils, parents, teacher and Head of the Village. There is also several of recommendation included in the research in order to reduce the dropout in primary school.